Ottoman stock returns during the Turco-Italian and Balkan Wars of 1910-1914 - Avni Önder Hanedar; Elmas Yaldız Hanedar (The European Association for Banking and Financial History (EABH), 2017)
In this paper, we use new historical data on the most popular stocks traded at the Istanbul bourse between 1910 and 1914, to examine the effect of wars on stock market prices. During this period, the Ottoman Empire was involved in the Turco-Italian and the Balkan wars, leading to massive land losses before the First World War. The data are manually collected from the available volumes of two daily Ottoman newspapers, Tercüman-ı Hakikat and Tanin. Our findings are quite surprising, as we observe only a temporary and small drop of prices, indicating little perceived risk by stock investors of the Istanbul bourse.
Keywords: G1; N25; N45; 330; the Istanbul stock exchange; stocks; the Turco-Italian war; the Balkan wars; structural breaks